The Impact Of Ethical Context On Employees In-Role Performance And Citizenship Behavior In Telecom Sector Of Pakistan: The Mediating Role Of Perceived Organizational Support - Waqas Ahmad WATTO; Abdul MONIUM; Qurban ALI; Ali IJAZ (Indonesia Strategic Sustainability, 2020)
The research purpose was to find out the influence of ethical context on certain employees’ behaviors (OCB-I, OCB-O In-role performance) working in the largest telecom companies of Pakistan. The most valuable asset for an organization is its employees, so the management must fix the factors that hinder their performance. In recent years, employees’ attitudes and behaviors in their work settings have remained the admiring topics in the field of organizational behavior. This study aims to investigate the impact of ethical culture and ethical climate on employee in-role performance and citizenship behavior while considering perceived organizational support as a mediating variable. The sample for this research is consisted of 800 employers and employees working in the top four cellular companies of large cities of Punjab, Pakistan. Statistical Package for Social Science version SPSS 16 is used for data analysis. To check the mediating and direct relationship between key variables of the study, correlation and regression analysis is used. Results indicate that both ethical culture and ethical climate have a positive relationship with employees’ outcomes i.e. in-role performance and organizational citizenship behavior. Perceived organizational support partially mediates the relationship between ethical context and employees’ outcomes.